4: Interactive Volume Rendering Method Using Dynamic Ray Casting for Autostereoscopic Display. (26th August 2021) - Li, Ruiyang; Huang, Tianqi; Zhang, Xinran; Liao, Hongen
Abstract : 3D volume is a common type of data collected in medical and life science domains. Existing visualization systems of volume data mainly use 2D displays. However, the complexity of volumes makes it challenging to comprehend the internal structures. Volume rendering with autostereoscopic displays can provide depth perception to improve understanding of complex structures. In this paper, we present an interactive volume rendering method for autostereoscopic display. The method is implemented through the combination of dynamic ray casting and hand gesture interaction. The proposed rendering algorithm brightens the organs intersected with an interaction plane and presents different appearances controlled by the user. We further build an application fusing the foreground virtual volume and the background actual human body. The application shows the prospects of our algorithm and system in education and clinical tasks.